Spatially-varying effects of built environment determinants on walking. (May 2019) - Kim, Suji; Park, Sungjin; Jang, Kitae
Highlights: This study explores the spatially-varying relationship between walking and built environment. Geographically Weighted Regression is utilized for a spatially-sensitive analysis. This approach enhanced the understanding about the influential pattern of variables at various geographic scales. The coefficients spatially vary depending on the site-specific characteristics.